Evaluation of Cancer Patient Satisfaction: A Transversal Study in Radiotherapy Department, Hassan II University Hospital, Fez, Morocco - Boujemaa EL Marnissi; Fouad Abbass; Hafida Charaka; Nawal Mouhoute; Abdelaziz Tritha; Touria Bouhafa; Khalid Hassouni (Advances in Public Health)
Patient satisfaction is an important quality outcome indicator of health care in the hospital setting. Patients are nowadays care-partners with caregivers. This relation is practically important for patients presenting chronic diseases, especially cancer. The aim of this study is to evaluate cancer patient satisfaction, treated at the Department of Radiotherapy in Hassan II University Hospital, and to study the different components of this satisfaction. A prospective transversal study was conducted between December 2016 and January 2017. Data was collected by three investigators based on structured interviews, a validated, anonymous and a standardized questionnaire. During this period, we have included 230 patients: 159 women (69.1%), 71 men (30.9%) and the sex ratio (women/men) was 2.23. Half of the investigated patients have never been schooled (52.61%). The majority had urban origin (71.3%) and 90% of patients declared being satisfied with the care at Radiotherapy department. 93.48% of cases recommended Radiotherapy department to other patients and 95.65% will want to continue their treatment at this department. Reception conditions were judged as favorable in 92.14%. Satisfaction rates regarding the availability of medical and paramedics, health-care workers were 86.52% and 83.9%, respectively. The quality of medical and paramedical care was judged as excellent or good in 78% cases. However, 44.34% of patients complained about the complexity of administrative formalities. 60.87% of cases judged that the waiting time was too long, whereas 31.4% of patients claimed that care-quality of their pain was insufficient or bad. The majority of patients declared being very satisfied or at least satisfied with different care services. For items that were judged as less satisfactory, some recommendations will be taken especially at the level of pain’s and palliative care as well as the organization of patients’ circuit inside the department. The satisfaction’s variations can be attributed to personally patients factors as well as systemic ones at the level of the hospital. Assessing and understanding these factors are essential in developing appropriate measures to improve patient satisfaction.